Human Liberation in the Indian Context - Thomas, R C (Journal of Dharma, 1983)
Sebastian Adayanthrath Human Liberation in the Indian Context Pune : The Students' Council, Jnana•Deepa Vidyapeeth, 1983, 256 pp.